Unveiling the plant growth-promoting and antifungal potential of Melissa officinalis endophytes: The integrative culture-dependent and metagenomic approaches - Vyacheslav Shurigin; Xiaoxuan Lu; Abdur Rashid Khan; Murad Muhammad; Ibad Ullah; Dilfuza Egamberdieva; Yang Yu; Li Li (Plant Science, 2026)

Redox-responsive goethite-modified biochar regulates cadmium and arsenic translocation in rice via irrigation-driven iron plaque dynamics - Iftikhar Ali Ahmad; Sharjeel Haider; Muhammad Mehran; Zaryab Murad; Adnan Mustafa; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Research, 2026)

Genome-wide identification and evolutionary characterization of the BTB and TAZ (BT) gene family in cultivated peanut (Arachis hypogaea L.) - Murad Ali; Muhammad Khurshid; Niaz Ali; Wei Zhang (Genetic Resources and Crop Evolution, 2026)

First molecular record of Panaeolus subbalteatus (Psathyrellaceae, Agaricales) from Pakistan - Saliha Rukhsar; Nousheen Yousaf; Sadaf; Mahneem Fazal; Muhammad Hanif; Murad Muhammad; Dilfuza Egamberdieva; Wen-Jun Li (Antonie van Leeuwenhoek, 2026)

Advances in Coated Fertilizers for Sustainable Agriculture - Muhammad Tahir Murad; Sadia Murad; Waqar Akram; Mohammad Shafiq u Rahman; Afroz Rais; Abdul Qadir; Dawood Atta (Journal of Soil Science and Plant Nutrition, 2026)

Enhancing Phytoremediation of Multi-Metal Contaminated Soil by Tagetes patula L. using Amycolatopsis tucumanensis KC 316 - Xiaoming Wang; Yajie Wu; Dejun Kong; Haotian Dong; Changyou Zhao; Murad Muhammad; Jing Zhang; Yuanchun Yang; Rui Liu; Shuai Wang; Aoli Zhang; Chunmei Lu; et al. (Journal of Environmental Sciences, 2026)

Impact of genetic composition on cows’ metabolic and fertility responses to thermal stress - Ihsan Ullah; Muhammad Subhan Qureshi; Raed M. Al-Atiyat; Shah Murad Khan; Ihtesham Ul Haq; Shabana Naz; Rifat Ullah Khan; Babar Maqbool; Marco Ragni; Ibrahim A. Alhidary (International Journal of Biometeorology, 2026)

Decoding the cold: integrated secretome profiling reveals extracellular adaptation mechanisms in Glaciozyma antarctica - Shuhaila Mat-Sharani; Farahayu Khairuddin; Nik Yusnoraini Yusof; Norfarhan Mohd-Assaad; Abdul Munir Abdul Murad; Farah Diba Abu Bakar; Nor Muhammad Mahadi; Nurdiana Nordin; Shazilah Kamaruddin (Extremophiles, 2026)

Harnessing Genetic Innovations for Climate-Resilient and High-Yield Crops: A Pathway to Sustainable Agriculture - Xu Qiao; Abdul Waheed; Cui Dong; Aishajiang Aili; Murad Muhammad; Hailiang Xu (Plant and Soil, 2026)

Determination of the Chemical Profile of Hibiscus rosa-sinensis L. Leaves Using Different Solvents and Evaluation of their Antioxidant, Antimitotic, and Antiproliferative Potentials - Sehrish Sadia; Muhammad Waheed; Tahira Rashid; Murad Muhammad; Huma Bashir; Fahim Arshad; Muhammad Iqbal; Abeer Hashem; Khalid F. Almutairi; Elsayed Fathi Abd-Allah (Journal of Pharmaceutical Innovation, 2026)

Gypsum-integrated, goethite-modified biochar enhances Cd and As immobilization in contaminated paddy soil under contrasting redox conditions - Iftikhar Ali Ahmad; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Geochemistry and Health, 2026)

Integrating chemical and microbial strategies for heavy metal remediation in contaminated soils: opportunities, challenges, and key factors - Muhammad Zeeshan Basheer; Xuhan Huang; Xiaolin Cai; Yanshan Cui; Murad Muhammad (Environmental Science and Pollution Research, 2026)

Harnessing traditional ethnoveterinary practices and medicinal plants for sustainable livestock health in arid rangelands - Shumaila Batool; Murad Muhammad; Minahal Fatima; Muhammad Waheed; Muqadas Batool; Mona F. A. Dawood; Abdul Wahab; Abdul Waheed; Khalid Abbas (Genetic Resources and Crop Evolution, 2025)

Exploring ethnoveterinary practices: a comprehensive study of medicinal plants in Bannu District, Khyber Pakhtunkhwa, Pakistan - Waseem Ahmed Khattak; Malka Saba; Minhas Elahi; Muhammad Anas; Qurban Ali Magsi; Rabia Tabassum; Adnan Khattak; Muhammad Majeed; Murad Muhammad (Genetic Resources and Crop Evolution, 2025)

Low frequency electrostatic wave dynamics in the subsolar magnetosheath of Venus: A theoretical framework with multi-ion and suprathermal electrons - Adil Murad; Muhammad Adnan; Shahida Parveen; Ikramullah; Fida Younus Khattak (Planetary and Space Science, 2025)

Jasmonic Acid: A Key Elicitor of Cold Stress Tolerance in Horticultural Crops - Izhar Ullah; Muhammad Hamza; Noor ul Ain; Heba I. Mohamed; Murad Muhammad; Yaqoob Sultan; Muskan Alam Khan; Abdul Basit (Journal of Plant Growth Regulation, 2025)

Plant root-mediated carbon sequestration and nutrient cycling in grassland ecosystems under land use and climate change - Abdul Waheed; Xu Qiao; Murad Muhammad; Yeernazhaer Yiremaikebayi; Xie Yingying; Hailiang Xu; Aishajiang Aili; Abdul Wahab (Agriculture, Ecosystems & Environment, 2025)

Quantitative exploration and conservation of the medicinal plant resources used by the inhabitants of Northern Pakistan - Murad Muhammad; Abdul Waheed; Abdul Wahab; Nimrah Ameen; Ibad Ullah; Muhammad Majeed; Muhammad Waheed; Khalid Rehman Hakeem; Mona F. A. Dawood; Wen-Jun Li (Genetic Resources and Crop Evolution, 2025)

Nutritional comparison of barley doubled haploid progenies with their parents - Bakht Nisa Mangan; Muhammad Siddique Lashari; Asif Ali Kaleri; Nazia Baloch; Abdul Wahid Baloch; Gulam Mujtaba Soomro; Murad Ali Magsi (Cereal Research Communications, 2025)

Endophytic Meyerozyma guilliermondii augmented growth attributes and metabolite production in Triticum aestivum under salinity stress - Zeeshan Khan; Muhammad Irshad; Anwar Hussain; Arshad Iqbal; Zamarud Shah; Waheed Murad; Eman R. Elsharkawy; Muhammad Nafees (Folia Microbiologica, 2025)

Evaluating water supply and demand growth in the Gulf Cooperation Council countries: projections and policy implications for sustainable water resources management - Amjad Aliewi; Muhammad Al Rashed; Dalal Sadeqi; Harish Bhandary; Ahmed Sefelnasr; Mohsen Sherif; Ahmed Murad; Dalal Alshamsi; Abdel Azim Ebraheem (Arabian Journal of Geosciences, 2025)

Food security and economic resilience of wild snake gourd (Trichosanthes cucumerina subsp. Cucumerina) under different host trees in subtropical managed forests - Muhammad Waheed; Fahim Arshad; Murad Muhammad; Abeer Hashem; Mohamad Alnafissa; Elsayed Fathi Abd-Allah; Valisher Sapayev (Agroforestry Systems, 2025)

Developing an ocean governance regime for China-Pakistan economic corridor: a comparison of the marine environmental legislation and policy framework by utilizing CRILL methodology - Shijun Zhang; Qian Wu; M Jahanzeb Butt; Minerva Batool; Muhammad Murad Zaib Butt (Frontiers in Marine Science, 2025)
Bilateralism in ocean governance is a novel concept that can be developed under the existing International Environmental Law (IEL) and United Nations Convention on the Law of the Sea (UNCLOS). This research paper suggested that bilateralism in ocean governance is one of the Agenda of Sustainable Development Goal 14 (SDG 14). This research paper utilized the methodology of a Comprehensive Review of Law and Relevant Literature (CRILL methodology) and developed a theoretical and legal framework for bilateral ocean governance with the elements of capacity building, adaptation, precautionary approach and participation. Under the given elements of CRILL methodology, this paper analyzed and compared the ocean governance mechanisms of China and Pakistan and proposed that under the China-Pakistan Economic Corridor (CPEC) of the Belt and Road Initiative (BRI), these two States can develop a bilateral framework of ocean governance for the protection of the marine environment, preservation of fisheries and mitigation of ocean acidification and sea level rise. The results of the CRILL methodology are presented in the form of a proposal that institutional coordination is essential for the effectiveness of bilateral ocean governance cooperation, which is China’s regional agenda of BRI. Through such development, the two States, China and Pakistan, can share the mutual economic benefits of ocean development and can have a strong voice in the global ocean agenda.

Simultaneous adsorption of cadmium and arsenic by goethite-modified rice straw-derived biochar in water and soil: interactive ion effects and co-adsorption mechanism - Iftikhar Ali Ahmad; Hongqing Hu; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Fei Miao; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Ayaz Ali (Environmental Monitoring and Assessment, 2025)

Impact of irrigation schedule and integrated nutrient management on wheat yield and nutrients uptake under semi-arid regions - Murad Ali; Abdul Bari; Muhammad Ibrahim; Iftikhar Ahmed; Uzair Ahmed; Rabia Zafar; Waqas Ahmad; Muhammad Saeed; Muhammad Khalid (Irrigation Science, 2025)

Role of plant growth-promoting rhizobacteria in sustainable agriculture: Addressing environmental and biological challenges - Abdul Wahab; Farwa Batool; Gholamreza Abdi; Murad Muhammad; Shahid Ullah; Wajid Zaman (Journal of Plant Physiology, 2025)

Dynamic approaches to ecological restoration in China's mining regions: A scientific review - Hailiang Xu; Abdul Waheed; Amannisa Kuerban; Murad Muhammad; Aishajiang Aili (Ecological Engineering, 2025)

Mitigation of cadmium stress by salicylic acid: Physiological and biochemical responses in NM-2006, NM-92, and Mash-88 mung bean varieties - Abdul Waheed; Qin Zhang; Hailiang Xu; Haitao Dou; Murad Muhammad; Aishajiang Aili; Mohammed O Alshaharni (Journal of Hazardous Materials, 2025)

Enhancing Wheat Yield and Zinc Biofortification through Synergistic Action of Potent Zinc-Solubilizing Bacteria and Zinc Sulfate in Calcareous Soil - Murad Ali; Iftikhar Ahmed; Munir Hussain Zia; Saira Abbas; Tariq Sultan; Muhammad Sharif (Agricultural Research, 2025)

Analysing Pakistan’s fisheries legislation and institutional framework: integrating Sustainable Development Goal 14 within the scope of International Fisheries Law - Liu Lina; Muhammad Murad Zaib Butt (Frontiers in Marine Science, 2025)
International Fisheries Law (IFL) provides innovative approaches to fisheries governance at national levels. The emergence of Sustainable Development Goal 14 (SDG 14) is phenomenal for fisheries because it creates new means for implementing IFL. Under SDG 14, fisheries governance for sustainable fisheries has become a complex and challenging task for any state. Developing States like Pakistan are struggling to achieve SDG 14 with new approaches to fisheries governance. The current situation of fisheries governance in Pakistan motivated the content of this research paper. This research paper adopted the comprehensive literature review (CLR) methodology to analyse existing fisheries governance mechanisms in Pakistan. Besides CLR, the paper also analysed a ‘case study’ on fisheries governance of Pakistan entitled ‘National Policy and Strategy for Marine Fisheries. Furthermore, one hundred sixty-seven research articles and national and international legislation on fisheries governance from 2010 - 2023 are analysed. The results of the CLR methodology suggested that an extensive integrated mechanism under a comprehensive framework should be developed for fisheries governance. The framework forwarded a policy mechanism incorporating sustainable development goals with SDG 14 that should be implemented coherently for sustainable fisheries. The discussion followed the analysis and suggested that regional to local and bottom-up and top-down approaches in fisheries governance are required to address the challenges to sustainable fisheries in Pakistan. The conclusion of the discussion portrayed that future research related to fisheries governance in Pakistan shall be based on the practical implementation of SDG 14.

Morphology and multigene phylogeny revealed four new species of Agaricus section Minores from Pakistan - Rab Nawaz; Waheed Murad; Muhammad Irshad; Hira Bashir; Shah Hussain (Mycological Progress, 2025)

Biochar in sustainable agriculture and Climate Mitigation: Mechanisms, challenges, and applications in the circular bioeconomy - Abdul Waheed; Hailiang Xu; Xu Qiao; Aishajiang Aili; Yeernazhaer Yiremaikebayi; Dou Haitao; Murad Muhammad (Biomass and Bioenergy, 2025)

Attributing rainfall and drought variability across climate vulnerable area of Pakistan: Perspective from different satellite and ground-based datasets - Mohammad Ilyas Abro; Ehsan Elahi; Murad Ali Khaskheli; Rashid Mustafa Korai; Mahdi Hassan; Asghar Ali Majidano; Bhai Khan Solangi; Faiz Muhammad Khokhar (Theoretical and Applied Climatology, 2025)

Navigating Climate Change: Exploring the Dynamics Between Plant–Soil Microbiomes and Their Impact on Plant Growth and Productivity - Murad Muhammad; Abdul Wahab; Abdul Waheed; Khalid Rehman Hakeem; Heba Ibrahim Mohamed; Abdul Basit; Muhammad Danish Toor; Yong‐Hong Liu; Li Li; Wen‐Jun Li (Global Change Biology, 2025)
Understanding the intricate interplay between plant and soil microbiomes and their effects on plant growth and productivity is vital in a rapidly changing climate. This review explores the interconnected impacts of climate change on plant–soil microbiomes and their profound effects on agricultural productivity. The ongoing rise in global temperatures, shifting precipitation patterns and extreme weather events significantly affect the composition and function of microbial communities in the rhizosphere. Changes in microbial diversity and activity due to rising temperatures impact nutrient cycling, microbial enzyme synthesis, soil health and pest and disease management. These changes also influence the dynamics of soil microbe communities and their capability to promote plant health. As the climate changes, plants' adaptive capacity and microbial partners become increasingly crucial for sustaining agriculture. Mitigating the adverse effects of climate change on plant growth and agricultural productivity requires a comprehensive understanding of the interconnected mechanisms driving these processes. It highlights various strategies for mitigating and adapting to environmental challenges, including soil management, stress‐tolerant crops, cover cropping, sustainable land and water management, crop rotation, organic amendments and the development of climate‐resilient crop varieties. It emphasises the need for further exploration of plant–soil microbiomes within the broader context of climate change. Promising mitigation strategies, including precision agriculture and targeted microbiome modifications, offer valuable pathways for future research and practical implementation of global food security and climate change.

The genus Hymenagaricus: phylogeny, time divergence estimation, and the description of three new species from Pakistan - Rab Nawaz; Waheed Murad; Muhammad Irshad; Shah Hussain (Mycological Progress, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Influence of Plant Growth Promoting Rhizobacteria (PGPR) on the Growth and Yield of Sunflower (Helianthus annus L.) Under Salt Stress - Shafi Ullah; Muhammad Ikram; Samina Sarfaraz; Ijaz ul Haq; Atika Khan; Zaryab Murad; Fazal Munsif (Journal of Crop Health, 2024)

Harnessing bacterial endophytes for environmental resilience and agricultural sustainability - Murad Muhammad; Abdul Wahab; Abdul Waheed; Heba Ibrahim Mohamed; Khalid Rehman Hakeem; Li Li; Wen-Jun Li (Journal of Environmental Management, 2024)

Sustainable Central Asia: Impact of fintech, natural resources, renewable energy, and financial inclusion to combat environmental degradation and achieving sustainable development goals - Yu Jie; Zeeshan Rasool; Abdelmohsen A. Nassani; Suchira Mattayaphutron; Muhammad Murad (Resources Policy, 2024)

Exogenous Potassium Silicate Improves Drought Tolerance in Cotton Genotypes by Modulating Growth, Gas Exchange and Antioxidant Metabolism - Muhammad Nazim; Xiangyi Li; Akash Tariq; Khurram Shahzad; Murad Muhammad; Zhang Dawei; Fanjiang Zeng (Journal of Crop Health, 2024)

Silicon nanoparticles: A novel approach in plant physiology to combat drought stress in arid environment - Muhammad Nazim; Xiangyi Li; Shazia Anjum; Fiaz Ahmad; Muqarrab Ali; Murad Muhammad; Khurram Shahzad; Lisha Lin; Usman Zulfiqar (Biocatalysis and Agricultural Biotechnology, 2024)

Erratum to: Endophytic Fungi as Potential Bio-Control Agents of Soil-Borne Pathogen - Murad Muhammad; Abdul Basit; Kashif Ali; Wen-Jun Li; Li Li; Heba I. Mohamed (Journal of Crop Health, 2024)

Endophytic Fungi as Potential Bio-Control Agents of Soil-Borne Pathogen - Murad Muhammad; Abdul Basit; Kashif Ali; Wen-Jun Li; Li Li; Heba I. Mohamed (Journal of Crop Health, 2024)

Agriculture and environmental management through nanotechnology: Eco-friendly nanomaterial synthesis for soil-plant systems, food safety, and sustainability - Abdul Wahab; Murad Muhammad; Shahid Ullah; Gholamreza Abdi; Ghulam Mujtaba Shah; Wajid Zaman; Asma Ayaz (Science of The Total Environment, 2024)

Long-term evaluation of rainfall in the arid region of Pakistan using multi-source data - Ehsan Elahi; Mohammad Ilyas Abro; Murad Ali Khaskheli; Ghulam Abbas Kandhro; Tasneem Zehra; Sikandar Ali; Muhammad Najam Shaikh; Barkat Ali Laghari; Mahdi Hassan; Mushtaque Ahmed Memon (Theoretical and Applied Climatology, 2024)

Biochemical and in silico structural characterization of a cold-active arginase from the psychrophilic yeast, Glaciozyma antarctica PI12 - Nik Yusnoraini Yusof; Doris Huai Xia Quay; Shazilah Kamaruddin; Mohd Anuar Jonet; Rosli Md Illias; Nor Muhammad Mahadi; Mohd Firdaus-Raih; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Extremophiles, 2024)

A review on endophytic fungi: a potent reservoir of bioactive metabolites with special emphasis on blight disease management - Murad Muhammad; Abdul Basit; Kashif Ali; Haris Ahmad; Wen-jun Li; Ayesha Khan; Heba I. Mohamed (Archives of Microbiology, 2024)

Identification and validation of restricted seed color polymorphic sites in Barley (Hordeum vulgare L.) using SNPs derived CAPS markers - Murad Ali; Danish Ibrar; Zuhair Hasnain; Afroz Rais; Shahbaz Khan; Kashf Mehmood; Sami Ullah; Ali Bakhsh; Safia Gul; Muhammad Musawir Khan; Waqar Khan; Muhammad Nisar; et al. (Genetic Resources and Crop Evolution, 2024)

Climate change reshaping plant-fungal interaction - Abdul Waheed; Yakoopjan Haxim; Waqar Islam; Mushtaq Ahmad; Murad Muhammad; Fatmah M. Alqahtani; Mohamed Hashem; Haron Salih; Daoyuan Zhang (Environmental Research, 2023)

Green means long life - green competencies for corporate sustainability performance: A moderated mediation model of green organizational culture and top management support - Murad Ali; Mehwish Malik; Muhammad Zafar Yaqub; Charbel Jose Chiappetta Jabbour; Ana Beatriz Lopes de Sousa Jabbour; Hengky Latan (Journal of Cleaner Production, 2023)

The deteriorating effects of cadmium accumulation on the yield and quality of maize crops - Naila Shah; Muhammad Irshad; Anwar Hussain; Asif Mehmood; Waheed Murad; Muhammad Qadir; Muhammad Awais; Mohib Shah; Naeem Khan (South African Journal of Botany, 2023)

Engineering legumes for drought stress tolerance: Constraints, accomplishments, and future prospects - Arshad Jalal; Kamran Rauf; Babar Iqbal; Rabia Khalil; Hayat Mustafa; Muhammad Murad; Farhan Khalil; Sulaiman Khan; Carlos Eduardo da Silva Oliveira; Marcelo Carvalho Minhoto Teixeira Filho (South African Journal of Botany, 2023)

Novel concept for water scarcity quantification considering nonconventional and virtual water resources in arid countries: Application in Gulf Cooperation Council countries - Muhammad Al Rashed; Ahmed Sefelnasr; Mohsen Sherif; Ahmed Murad; Dalal Alshamsi; Amjad Aliewi; Abdel Azim Ebraheem (Science of The Total Environment, 2023)

Assessing conservation attitudes of mountain communities under different resource management regimes in northern Pakistan - Muhammad Zafar Khan; Sayeed Murad Shah; Athar Ali Khan (Environment, Development and Sustainability, 2023)

Can heat shock protein 70 (HSP70) serve as biomarkers in Antarctica for future ocean acidification, warming and salinity stress? - Nur Athirah Yusof; Makdi Masnoddin; Jennifer Charles; Ying Qing Thien; Farhan Nazaie Nasib; Clemente Michael Vui Ling Wong; Abdul Munir Abdul Murad; Nor Muhammad Mahadi; Izwan Bharudin (Polar Biology, 2022)
The Antarctic Peninsula is one of the fastest-warming places on Earth. Elevated sea water temperatures cause glacier and sea ice melting. When icebergs melt into the ocean, it “freshens” the saltwater around them, reducing its salinity. The oceans absorb excess anthropogenic carbon dioxide (CO 2 ) causing decline in ocean pH, a process known as ocean acidification. Many marine organisms are specifically affected by ocean warming, freshening and acidification. Due to the sensitivity of Antarctica to global warming, using biomarkers is the best way for scientists to predict more accurately future climate change and provide useful information or ecological risk assessments. The 70-kilodalton (kDa) heat shock protein (HSP70) chaperones have been used as biomarkers of stress in temperate and tropical environments. The induction of the HSP70 genes ( Hsp70 ) that alter intracellular proteins in living organisms is a signal triggered by environmental temperature changes. Induction of Hsp70 has been observed both in eukaryotes and in prokaryotes as response to environmental stressors including increased and decreased temperature, salinity, pH and the combined effects of changes in temperature, acidification and salinity stress. Generally, HSP70s play critical roles in numerous complex processes of metabolism; their synthesis can usually be increased or decreased during stressful conditions. However, there is a question as to whether HSP70s may serve as excellent biomarkers in the Antarctic considering the long residence time of Antarctic organisms in a cold polar environment which appears to have greatly modified the response of heat responding transcriptional systems. This review provides insight into the vital roles of HSP70 that make them ideal candidates as biomarkers for identifying resistance and resilience in response to abiotic stressors associated with climate change, which are the effects of ocean warming, freshening and acidification in Antarctic organisms.

Estimation of a trend of meteorological and hydrological drought over Qinhuai River Basin - Mohammad Ilyas Abro; Ehsan Elahi; Ram Chand; Dehua Zhu; Jan Muhammad; Muhammad Rafique Daudpoto; Abdul Majid Soomro; Murad Ali Khaskheli (Theoretical and Applied Climatology, 2022)

Response of root development and nutrient uptake of two chinese cultivars of hybrid rice to nitrogen and phosphorus fertilization in Sichuan Province, China - Guotao Yang; Farhan Nabi; Sumbal Sajid; Abdul Rasheed Kaleri; Ali Murad Jakhar; Liang Cheng; Martin Raspor; Noor Muhammad; Jun Ma; Yungao Hu (Molecular Biology Reports, 2021)
Background Chemical fertilization helped modern agriculture in grain yield improvement to ensure food security. The response of chemical fertilization for higher hybrid rice production is highly dependent on optimal fertilization management in paddy fields. To assess such responses, in the current work we examine the yield, root growth, and expression of related genes responsible for stress metabolism of nitrogen (N) and phosphorus (P) in two hybrid-rice cultivars Deyou4727 (D47) and Yixiangyou2115 (Y21). Methods and results The experiment followed four nitrogen (N) (N 0 , N 60 , N 120, and N 180 kg/ha) and phosphorus (P) (P 0 , P 60 , P 90 , and P 120 kg/ha) fertilizer levels. The grain yield in D47 was more sensitive to nitrogen application, while Y21 was more sensitive to phosphorus application, which resulted in comparatively higher biomass and yield. Our findings were corroborated by gene expression studies of glutamine synthetase OsGS1;1 and OsGS1;2 and phosphate starvation-related genes PHR1 and SPX , confirming sensitivity to N and P application. The number of roots was less sensitive to nitrogen application in D47 between N 0 and N 60 , but the overall nutrient response difference was significantly higher due to the deep rooting system as compared to Y21. Conclusions The higher yield, high N and P use efficiency, and versatile root growth of D47 make it suitable to reduce unproductive usage of N and P from paddy fields, improving hybrid rice productivity, and environmental safety in the Sichuan basin area of China.

Pseudocitrobacter anthropi reduces heavy metal uptake and improves phytohormones and antioxidant system in Glycine max L. - Husna; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Amjad Iqbal; Waheed Murad; Muhammad Irshad; Muhammad Qadir; Ho-Youn Kim (World Journal of Microbiology and Biotechnology, 2021)

Hydrological appraisal of rainfall estimates from radar, satellite, raingauge and satellite–gauge combination on the Qinhuai River Basin, China - Muhammad Ilyas Abro; Dehua Zhu; Ming Wei; Asghar Ali Majidano; Murad Ali Khaskheli; Zain Ul Abideen; Muhammad Sohail Memon (Hydrological Sciences Journal, 2019)

Achieving an environmentally sustainable outcome for the Gulpur hydropower project in the Poonch River Mahaseer National Park, Pakistan - Cate Brown; Vaqar Zakaria; Alison Joubert; Muhammad Rafique; Jahanzeb Murad; Jackie King; Jessica Hughes; Pablo Cardinale; Leeanne Alonzo (Sustainable Water Resources Management, 2019)

Biochemical and structural characterization of a novel cold-active esterase-like protein from the psychrophilic yeast Glaciozyma antarctica - Noor Haza Fazlin Hashim; Nor Muhammad Mahadi; Rosli Md Illias; Shevin Rizal Feroz; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Extremophiles, 2018)

Ecotoxicological evaluation of two anti-dandruff hair shampoos using Lemna minor - Azizullah Azizullah; Shakirullah Khan Shakir; Shahana Shoaib; Halima Bangash; Nadia Taimur; Waheed Murad; Muhammad Khan Daud (Environmental Monitoring and Assessment, 2018)

Structure Prediction of a Novel Exo-β-1,3-Glucanase: Insights into the Cold Adaptation of Psychrophilic Yeast Glaciozyma antarctica PI12 - Salimeh Mohammadi; Sepideh Parvizpour; Jafar Razmara; Farah Diba Abu Bakar; Rosli Md Illias; Nor Muhammad Mahadi; Abdul MunirAbdul Murad (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Mix cropping of legume (Vigna Radiata) and non-legume (Zea Mays) crops alleviates water stress as revealed by growth and biochemical parameters - Kalim Ullah Khan; Waheed Murad; Azizullah Azizullah; Hazir Rahman; Muhammad Daud Khan (Acta Physiologiae Plantarum, 2017)

Screening of Potato Cultivars to Potato Mop-Top Virus in Northwestern Pakistan - Muhammad Arif; Ghazala Ruby; Anayatur Rehman; Murad Ali; Shamsur Rehman (Potato Research, 2016)

Biofunctional properties of Eruca sativa Miller (rocket salad) hydroalcoholic extract - Khushbakht Sultan; Muhammad Zakir; Haroon Khan; Abdur Rauf; Noor Ul Akber; Murad Ali Khan (Natural Product Research, 2016)

Erratum to: Production of an oligosaccharide-specific cellobiohydrolase from the thermophilic fungus Thielavia terrestris - James Sy-Keen Woon; Mukram Mohamed Mackeen; Amirul Husna bin Sudin; Nor Muhammad Mahadi; Rosli Md Illias; Abdul Munir Abdul Murad; Farah Diba Abu Bakar (Biotechnology Letters, 2016)

Production of an oligosaccharide-specific cellobiohydrolase from the thermophilic fungus Thielavia terrestris - James Sy-Keen Woon; Mukram Mohamed Mackeen; Amirul Husna bin Sudin; Nor Muhammad Mahadi; Rosli Md Illias; Abdul Munir Abdul Murad; Farah Diba Abu Bakar (Biotechnology Letters, 2016)

Microbial contamination of drinking water in Pakistan—a review - Farhat Nabeela; Azizullah Azizullah; Roqaia Bibi; Syeda Uzma; Waheed Murad; Shakirullah Khan Shakir; Waheed Ullah; Muhammad Qasim; Donat-Peter Häder (Environmental Science and Pollution Research, 2014)

Molecular cloning, expression and characterisation of Afp4, an antifreeze protein from Glaciozyma antarctica - Noor Haza Fazlin Hashim; Suhaila Sulaiman; Farah Diba Abu Bakar; Rosli Md Illias; Hidehisa Kawahara; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Polar Biology, 2014)

Occurrence of potato mop-top virus in Northwest of Pakistan - Muhammad Arif; Murad Ali; Anayatur Rehman; Muhammad Fahim (European Journal of Plant Pathology, 2013)

Isolation of long-chain esters from the rhizome of Polygonatum verticillatum by potent tyrosinase inhibition - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Izhar-ul-Haq; Naveed Muhammad; Rukhsana Ghaffar (Medicinal Chemistry Research, 2013)

Thermal stress responses in Antarctic yeast, Glaciozyma antarctica PI12, characterized by real-time quantitative PCR - Sook Yee Boo; Clemente Michael Vui Ling Wong; Kenneth Francis Rodrigues; Nazalan Najimudin; Abdul Munir Abdul Murad; Nor Muhammad Mahadi (Polar Biology, 2013)

Characterization of Afp1, an antifreeze protein from the psychrophilic yeast Glaciozyma antarctica PI12 - Noor Haza Fazlin Hashim; Izwan Bharudin; Douglas Law Sie Nguong; Sakura Higa; Farah Diba Abu Bakar; Sheila Nathan; Amir Rabu; Hidehisa Kawahara; Rosli Md. Illias; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Extremophiles, 2013)

Antimalarial and free radical scavenging activities of rhizomes of Polygonatum verticillatum supported by isolated metabolites - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Inamullah Khan; Manzoor Ahmad; Naveed Muhammad; Afsar Khan (Medicinal Chemistry Research, 2012)

TLR4 polymorphisms and disease susceptibility - Mamoona Noreen; Muhammad Ali A. Shah; Sheeba Murad Mall; Shazia Choudhary; Tahir Hussain; Iltaf Ahmed; Syed Fazal Jalil; Muhammad Imran Raza (Inflammation Research, 2012)

A mutant l-asparaginase II signal peptide improves the secretion of recombinant cyclodextrin glucanotransferase and the viability of Escherichia coli - Noor Faizah Ismail; Salehhuddin Hamdan; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Amir Rabu; Farah Diba Abu Bakar; Peter Klappa; Rosli Md. Illias (Biotechnology Letters, 2011)

Expression and characterization of Trichoderma virens UKM-1 endochitinase in Escherichia coli - Nadiawati Alias; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Farah Diba Abu Bakar; Nik Azmi Nik Mahmood; Rosli Md Illias (World Journal of Microbiology and Biotechnology, 2009)